Teachers’ persistence in resource-constrained and conflict-affected communities in the Philippines - Joseph Dave M. Pregoner; Mark M. Alipio; Grace Meroflor A. Lantajo; Ivy Joy D. Ganancial; Flordelis A. Sedo; Maria Rizalie S. Lindo; Mildred P. Galvez; Lilibeth R. Lozada; Reanne D. Leopardas (Institute of Advanced Engineering and Science, 2026)
This study interrogates why teachers persist in the Philippines’ resource-constrained, conflict-affected “last-mile” schools, reframing retention beyond deficit narratives of burnout and attrition. Using a descriptive phenomenological design guided by Colaizzi, we conducted semi-structured Zoom interviews with 15 public-school teachers in geographically isolated municipalities of Lanao del Norte and Lanao del Sur between September and November 2024, supplemented by brief reflective journals and supported by member checking and an audit trail to secure trustworthiness. Analysis reveals persistence as a moral-relational practice braided from duty to students’ futures, faith-inflected vocation, thick bonds of belonging with colleagues and communities, and a professional identity sustained by visible learner impact and craft growth, continually negotiated against material scarcity, bureaucratic load, and ambient insecurity through pragmatic coping and family responsibility. These findings challenge rational-choice explanations by showing that staying endures less through marginal incentives than through reinforced meaning infrastructures and everyday dignifying leadership. The study contributes a humanistic account of professional endurance in fragile settings and suggests policy directions that prioritize localized psychosocial support, recognition, and paperwork rationalization to strengthen the ecologies that already hold teachers in place.